Enhancing transit polio vaccination in collaboration with targeted stakeholders in Kaduna State, Nigeria: Lessons learnt: 2014–2015. Issue 43 (10th October 2016) - Musa, Audu; Abba, Bashir; Ningi, Adamu M.I.; Gali, Emanuel; Bawa, Samuel; Manneh, Fadninding; Mkanda, Pascal; Banda, Richard; Yehuluashet, Yared G.; Tegegne, Sisay G.; Umeh, Gregory; Nsubuga, Peter; et al.
Highlights: Many children are often missed by vaccination team due to population movements. Transit vaccination proved a very useful approach to targeting these children. Engagement of stakeholders enhanced transit polio vaccination in Kaduna. Abstract: Introduction: In Kaduna State of Nigeria, the high influx of people from neighboring states with eligible children for polio vaccination represents a significant proportion of the target population. Many of these children are often missed by the vaccination team. The purpose of the study was to determine the contribution of targeted stakeholders in transit polio vaccination. Methods: We used the trends of vaccinated children at transit points, motor parks and markets, well as total children vaccinated by transit teams in Chikun, Igabi and Sabon Gari Local Government Areas (LGAs) of Kaduna State, Nigeria, four rounds before and after the introduction of transit polio vaccination with targeted stakeholders in Kaduna State. Results: A total of 87, 502 under-5 children were vaccinated by the various transit teams in the three LGAs, which accounted for 3.2% of the total 2, 781, 162 children vaccinated by the three LGAs. For transit point vaccination, the number of vaccinated children increased from 1026 to 19, 289 (302%), while motor park vaccination increased from 1289 to 4106 (318%) and market vaccination increased from 10, 488 to 14, 511 (138%), four rounds after the introduction of transit polio vaccination with targeted stakeholders. Conclusion: Engagement of targeted stakeholders significantly enhanced transit polio vaccination in Kaduna State, Nigeria.